Rol del psicólogo en las instituciones carcelarias y penitenciarias de Bogotá. (2001)
This research describes the psychologist?s roll in the jails and penitentiaries institutions in Bogota. The variables selected were the psychologist?s roll, the characteristics of their academic background, and their social, demographic and labor factors. The sample was nine psychologists that worked in these institutions. The instrument was a survey to obtain information related to their work characteristics that has 36 items and five factors. The data analysis used descriptive statistical and the results showed that the main characteristics of these psychologists are: mostly married women, middle age (35 years old), who have eight years since graduation. Also, they have a permanent employment and are working as psychologists in these institutions.